Eksistensi Delik Adat dalam Kontestasi Hukum Pidana Indonesia - M. Misbahul Mujib (UIN Sunan Kalijaga Yogyakarta, 2013)
Indigenous offense is an act that violates the sense of justice and propriety inpublic life, sahingga cause disruption of public peace and order to restore balance, thenSo, Customary law offense is a whole unwritten law that determines the existence of violations of customary deeds and all attempts to restorea state of equilibrium is disturbed by such actions.there is the customary reactions.encouraged the emergence of an ongoing debate since the beginning of the independence ofIndonesia on whether custom could be one source of law in the Indonesian constitution. Therefore, the focus in this study is the existence of Indigenous offense in Indonesiancriminal law system. The conclusion in this paper can be said that the offense is a violation of Indigenous customary criminal and civil. In solution, preferably an elementHowever, Indigenous offense hasof peace through justice of the peace as the controlling offense Indigenous village. If not tercapa peace, then the elders can provide appropriate sanctions and the background dueto the violation.